Reading as a human right (a first approach) - Flores Giménez, Fernando (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
The article considers the possibility of approaching reading as a human right. For this purpose, it is subjected to the questions that the general theory of rights uses to identify the actions that contain the requirements to be considered as such: why should reading be a right, to what purpose it would respond, what is its nature, and to which limits it should be subjected. In this first approach, the text focuses on the object of reading, on that part of reading that should be protected by the human right, specifically its profile as a freedom and its nature as a provision. Finally, and as a link for a future text, the subjects of the right to read are identified: the holders, those obliged by it and the ‘indispensable’.